A study of stress singularities arising at the multi-material interface in a V-notched bending plate. (July 2017) - Zhou, Zhenhuan; Xu, Wang; Leung, Andrew Y.T.; Rong, Dalun; Xu, Xinsheng
Graphical abstract: Highlights: We find the analytical solutions of V-notched multi-material bending plate. We define new fracture parameters (GSIFs) to evaluate multi-material interface. We extend the finite element discretized symplectic method to compute the GSIFs. New results are presented and can be used as benchmarks. The method shows a good reliability and high accuracy in the entire process. Abstract: Stress singularities arising at the multi-material interface in a V-notched plate under bending are studied in the frame work of a Hamiltonian-based method. Exact solutions of V-notched multi-material plates are expressed in an analytical symplectic series. Newly defined generalized stress intensity factor (GSIF) are introduced to evaluate fracture behaviors of the V-notched plate. A highly accurate finite element discretized symplectic method is employed to compute the GSIFs and to obtain the explicit expressions of singular stresses near the notch tip. Comparisons are presented to show the accuracy and efficiency of the present work. Some new results are also provided.